Are They Really Neglected? A Look at Worker Perceptions of Neglect Through the Eyes of a National Data System - Fox, Kathleen Earle (First Peoples Child & Family Review, 2004)
A follow up to a two-year study of abuse and neglect of American Indian children looks at differences in perceptions of neglect of American Indian children found in the National Child Abuse and Neglect Data System (NCANDS). Findings from an analysis of 17,000 cases of neglect of white or American Indian children were that the neglect of American Indian children, compared to Caucasian children, was more often associated with foster care placement, juvenile court petition, alcohol abuse of child or caretaker, violence in the family, and family receipt of public assistance. The neglect of Caucasian children, when compared to American children, was more often associated with family preservation services, child or adult mental or physical problem, and inadequate housing. These data, from the 1995-1999 NCANDS, appear to conﬁrm stereotypical assignations of neglect to American Indian families. This study supports the need for the direct participation of sovereign Indian nations in child protective investigation, treatment, and data collection, in order to create a more complete data system that will provide accurate numbers and characteristics of abused and neglected American Indian children.